2016
DOI: 10.1111/ases.12300
|View full text |Cite
|
Sign up to set email alerts
|

Sternotomy versus video‐assisted thoracoscopic surgery for thymectomy of myasthenia gravis patients: A meta‐analysis

Abstract: Based on the results of this meta-analysis of retrospective cohort studies, VATS increases surgical safety and achieves an equal surgical efficacy to TS, but TS has a shorter operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
(35 reference statements)
3
15
0
1
Order By: Relevance
“…In this study, we examined whether our VATS procedure is superior to sternotomy in terms of invasiveness and efficacy for MG. In regard to invasiveness as reported by others (18,19), our data also showed this approach to be less invasive than sternotomy in terms of blood loss, postoperative length of stay, and the CRP value on postoperative day 1. Some reasons for the lower amount of bleeding include the delicate movements used to avoid hemorrhage that are peculiar to the VATS procedure, the pressure of CO 2 insufflation on the small vessels, and no sternal splitting.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, we examined whether our VATS procedure is superior to sternotomy in terms of invasiveness and efficacy for MG. In regard to invasiveness as reported by others (18,19), our data also showed this approach to be less invasive than sternotomy in terms of blood loss, postoperative length of stay, and the CRP value on postoperative day 1. Some reasons for the lower amount of bleeding include the delicate movements used to avoid hemorrhage that are peculiar to the VATS procedure, the pressure of CO 2 insufflation on the small vessels, and no sternal splitting.…”
Section: Discussionsupporting
confidence: 88%
“…The efficacy of minimally invasive surgery for MG remains controversial. However, some reports show that in terms of remission rates, minimally invasive surgery is equally or more efficacious in MG than the trans-sternal approach (18,19). Our data indicated that importantly, the efficacy of extended thymectomy using our approach is at least not inferior to that of extended thymectomy via sternotomy ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…1 Through a rigorous statistical analysis of data retrieved from one of the most relevant databases worldwide, the authors provided evidence that minimally invasive surgery performed with either video-assisted thoracoscopic surgery (VATS) or robotic-assisted thoracoscopic surgery (RATS) techniques can achieve rates of thymoma complete resection similar to those achieved with open surgery. 1 These findings, in addition to further recent evidence supporting the safety and efficacy of VATS in thymomas and other thymus diseases, [2][3][4] explain the fact that use of minimally invasive surgery has been increasing substantially over time 1 and will potentially represent the definitive standard in the future. To achieve such legitimacy, further technological improvements to the current techniques are necessary.…”
Section: To the Editormentioning
confidence: 96%
“…The choice of the first side of the thorax to be approached varies according to the surgeon's experience and preference. The intraoperative steps may also vary: some surgeons prefer to start dissection from the right side and divide the thymic veins from the left, while others approach the thymic veins from the left first, and some authors start dissecting the thymic veins from the right [6,9,10] .…”
Section: Introductionmentioning
confidence: 99%